Modelling and Simulation of Ideal and Torque-Limited Devices to Assist Elderly Walking - Khanna, Tanaya (Université d'Ottawa / University of Ottawa, 2021)
Interest in wearable exoskeletons is increasing as the demand increases for assistive technologies that meet the needs of the elderly population. Decreased mobility and loss of independence are major concerns as the global trend of increasing mean population continues. Past research has focused on walking assistance exoskeletons to maintain, restore, and enhance mobility. However, in the current state of the art, little is understood about how to best assist elderly individuals specifically. The results from studies of younger adults may not apply because gait patterns of elderly individuals often differ from those of the younger population. This thesis investigates the effect of ideal and torque-limited assistance on metabolic energy consumption when assistance is applied at the ankle, knee, and hip joints of elderly individuals during overground gait using the OpenSim software. The simulated ideal devices have no mass and can generate unlimited torque, representing a best-case scenario where the maximum amount of metabolic energy is saved given the observed kinematics. This simulation strategy provides an approximation of the upper limit for assistive devices that aim to reduce metabolic cost. The simulations with torque limits were generated to investigate the effect of this practical limitation. This study focuses on reducing metabolic cost as fatigue during walking is a fundamental concern in the elderly population. Simulations of 10 elderly participants walking at a self-selected, comfortable speed were generated using the Computed Muscle Control Tool in OpenSim. Ideal and torque-limited devices were added bilaterally at the ankle, knee, and hip joints of the 10 corresponding musculoskeletal models. The device torque profiles and changes in the activity and metabolic power consumed by the muscles were computed. The results of this study suggest that providing hip flexion/extension assistance to elderly individuals may result in substantially greater metabolic savings compared to assistance provided at the knee or ankle. When compared to the unassisted simulations, the use of an ideal hip flexion/extension device resulted in a 24% average reduction in metabolic cost, with a loss in effectiveness of only 2 percentage points when the maximum torque was limited to 50% of the peak ideal torque; ideal hip abduction/adduction, knee flexion/extension, and ankle plantarflexion/dorsiflexion devices saved 15%, 20%, and 12%, respectively, on average. Computational studies of assistive devices can provide valuable insights for engineers who are developing walking assist exoskeletons for elderly individuals.
Keywords: Wearable exoskeletons; Elderly gait; Ideal assistance; Torque-limited assistance; OpenSim; Computed Muscle Control Tool; Metabolic cost